THE ROLE OF MAHKAMAH AL-LUGHAH IN IMPROVING ARABIC SPEAKING COMPETENCE AT NURUL HAKIM MODERN BOARDING SCHOOL IN TEMBUNG - Harahap, Dita Andini; Nasution, Sahkholid (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan & Bahasa Arab, 2025)
This study aims to analyze the role of Mahkamah al-Lughah in improving Arabic speaking competence (maharah al-kalam) at Pondok Pesantren Modern Nurul Hakim Tembung. The background of this research is based on the low speaking ability of santriyati due to lack of motivation and ineffective learning methods. Mahkamah al-Lughah, which is a judicial simulation in Arabic, is an innovative approach in the pesantren environment to train santri to think critically, compose arguments, and actively use Arabic in daily life. This research uses a descriptive qualitative approach with data collection methods through observation, interviews, and documentation. The results showed that Mahkamah al-Lughah is effective in improving the speaking skills of santri because it is supported by a conducive language environment, exemplary management and teachers, and systematic procedures through the role of jasus (language scouts). The inhibiting factors found include a lack of self-confidence and the influence of local languages in the association of santri. This study recommends strengthening the role model and motivation from the teachers as well as developing evaluation procedures that are more educational and constructive.